Literatur Sistematik : Pengintegrasian Etnomatematika Berbasis Augmented Reality pada Pemahaman Konsep Bangun Ruang - Andi Trisno Trisno; Suradi; Rosidah (FKIP Universitas Mataram, 2025)
This study aims to analyze the results of a systematic literature review (SLR) concerning the integration of ethnomathematics-based Augmented Reality (AR) in geometry learning, particularly focusing on cube and cuboid concepts. This approach reviews the effectiveness of combining local cultural contexts with digital technology to enhance students’ conceptual understanding of mathematics. Literature was collected using the Publish or Perish tool from Scopus and Sinta databases and evaluated following the PRISMA guidelines to ensure relevance and eligibility. From 200 identified articles, 20 studies met the inclusion criteria and were further analyzed. The findings reveal that AR significantly improves students’ spatial visualization, understanding of volume and surface area, and learning motivation. Meanwhile, ethnomathematics serves as a contextual medium linking mathematical concepts to local culture, making learning more meaningful and character-building. The integration of both approaches fosters interactive, contextual, and culturally relevant learning while introducing the concept of symmetry groups through cultural exploration and digital visualization. The study recommends the development of an AR-ethnomathematics-based learning model that explicitly integrates symmetry group concepts to deepen students’ geometric understanding and strengthen cultural values in mathematics education